Results of Influenza Vaccination: Short Follow-Up Study of a Turkish Population - Ozturk,Guzin Zeren (2020)
Abstract INTRODUCTION: The trivalent inactivated influenza vaccine was approved for use in Turkey during the 2018-2019 influenza season. We evaluated beliefs regarding the vaccine and vaccination outcomes in a Turkish population. METHODS: Individuals who were vaccinated with the trivalent inactivated influenza vaccine between November 1 and December 31, 2018, at the Sisli Hamidiye Training and Research Hospital in Istanbul, Turkey, were included in this study. A 15-item questionnaire was completed by a physician during a face-to-face interview with the participants. All participants were followed during the 2018-2019 influenza season through May 2019. The participants were instructed to consult the same physician in case of sudden illness. Participants’ beliefs and outcomes were assessed by their vaccination status for the 2017-2018 influenza season. RESULTS: A total of 150 participants were recruited. Their median age was 66 (range, 22-88) years. During the 2017-2018 influenza season, 4.1% had been hospitalized, 53.5% had developed an upper respiratory disease (URD), and 16.2% had been diagnosed with pneumonia. There were no cases of influenza, pneumonia, or hospitalization in the 2019 season; 49.3% of the participants developed a URD (n = 74). Among participants who had been vaccinated during both influenza seasons, 47.5% had had and/or developed a URD, with a higher number of cases during the 2018-2019 season. CONCLUSIONS: After vaccination, no cases of influenza, hospitalization, and pneumonia were observed and the incidence of URD decreased compared with that of the previous season.